Fleming's penicillin producing strain is not Penicillium chrysogenum but P. rubens - J. Houbraken; J.C. Frisvad; R.A. Samson (IMA Fungus)
Penicillium chrysogenum is a commonly occurring mould in indoor environments and foods, and has gained much attention for its use in the production of the antibiotic penicillin. Phylogenetic analysis of the most important penicillin producing P. chrysogenum isolates revealed the presence of two highly supported clades, and we show here that these two clades represent two species, P. chrysogenum and P. rubens. These species are phenotypically similar, but extrolite analysis shows that P. chrysogenum produces secalonic acid D and F and/or a metabolite related to lumpidin, while P. rubens does not produce these metabolites. Fleming's original penicillin producing strain and the full genome sequenced strain of P. chrysogenum are re-identified as P. rubens. Furthermore, the well-known claim that Alexander Fleming misidentified the original penicillin producing strain as P. rubrum is discussed.